IMAGES SEGMENTATION BASED CONTOUR USING EVCA APPROACH, EVOLUTIONARY CELLULAR AUTOMATA - SLATNIA, S.; KAZAR, O. (Courrier du Savoir, 2014)
We use an evolutionary process to seek a specialized powerful rule of Cellular Automata (CA) among a set of best rules for extracting edges in a given black-white image. This best set of local rules determines the future state of CA in an asynchronous way. The Genetic Algorithm (GA) is applied to search the best CA rules that can realize better the edge detection